A study of motives for tobacco and alcohol use among high school students in Hungary - Pikó Bettina; Varga Szabolcs; Wills Thomas A. (2015)
Motives may be an important influence for substance use among youth. The goal of this research was to study the relation of social, self-enhancement, boredom relief and affect regulation motives to smoking and drinking in a sample of Eastern European high school students and to examine variation in the effects of these motives by gender. Our sample involved 500 students (ages 14–20 years) from three high schools in a large city in Hungary. Multiple logistic regression analyses examined the relation between motives and substance user status. Social motives were significantly related to both smoking and drinking (except for boys’ smoking). Affect regulation motives were a significant predictor of smoking; in addition, boredom relief was a significant motive for smoking among boys. Mother’s educational level was inversely related to youth substance use, whereas father’s education was positively related to alcohol use among girls. School-based prevention programs should include cognitive education and social skills training to counter perceived benefits of substance use. Further research is needed to clarify the relation of alcohol use to parental education. © 2015 Springer Science+Business Media New York